MAXIMA-1: A Measurement of the Cosmic Microwave Background Anisotropy on angular scales of 10 arcminutes to 5 degrees - Hanany, S; Ade, P; Balbi, A; Bock, J; Borrill, J; Boscaleri, A; Bernardis, P; Ferreira, P; Hristov, V; Jaffe, A; Lange, A; Lee, A; et al. (2000)
We present a map and an angular power spectrum of the anisotropy of the cosmic microwave background (CMB) from the first flight of MAXIMA. MAXIMA is a balloon-borne experiment with an array of 16 bolometric photometers operated at 100 mK. MAXIMA observed a 124 square degrees region of the sky with 10 arcminute resolution at frequencies of 150, 240 and 410 GHz. The data were calibrated using in-flight measurements of the CMB dipole anisotropy. A map of the CMB anisotropy was produced from three 150 and one 240 GHz photometer without need for foreground subtractions. Analysis of this CMB map yields a power spectrum for the CMB anisotropy over the range 36 < l < 785. The spectrum shows a peak with an amplitude of 78 +/- 6 micro-Kelvin at l ~ 220 and an amplitude varying between ~40 micro-Kelvin and ~50 micro-Kelvin for 400 < l < 785.